Menanamkan Pemahaman Etika Berkomunikasi Kepada Gen Z Di SMA Negeri 1 Cepogo - Firmansyah, Yuliyanto Adi; Yulianti, Naila Dwi; Meilina, Assyifa Fatma; Khotimah, Arini Khusnul; Hartini, Sri (Journal Of Human And Education (JAHE), 2025)
This community service was motivated by problems in communication ethics at SMA Negeri 1 Cepogo. Lack of understanding of ethics in communication causes inappropriate use of language in communication. There is a change in communication behavior between the millennial generation and generation z in the digital era, which has shifted from the previous era. Based on this information, the results obtained from this service are that students know how to deal with people who have made mistakes in using social media. Based on these problems, we are trying to provide a solution by providing socialization on understanding communication ethics. The method used in carrying out this community service is in the form of counseling in the form of presentation of material from resource persons as well as question and answer discussions from counseling participants about the importance of understanding communication ethics and the need to apply ethics in social life. The results obtained from this service are that students know how to communicate using correct language, both in the real world and on social media. Students know good and bad behavior that should be avoided so as not to fall into the use of bad language when communica.